IOT BASED SMART PARKING MANAGEMENT SYSTEM - Mr.D.SATYANARAYANA , Mr.M.RAMANA REDDY , PASUPULA SWATHI, SHAIK JAMEER BASHA, KUNDURU SUBHASHINI, RODDA VASANTHA KUMARI, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
In recent times the concept of smart cities have gained grate popularity. Thanks to the evolution of theInternet of things the idea of smart city now seems to be achievable. Consistent efforts are being made inthe field of IoT in order to maximize the productivity and reliability of urban infrastructure. Problems suchas, traffic congestion, limited car parking facilities and road safety are being addressed by IoT